High intraocular pressure : a comparative study between Obstructive Sleep Apnea (OSA) and non-OSA subjects - Marina Mat Baki,; Mohd Tahir J,; Mawaddah Azman,; Asma Abdullah,; Mohd Razif MY,; Jemaima Che Hamzah, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Obstructive Sleep Apnoea (OSA) affects 2-5% of the middle-aged population and is a potentially life-threatening condition. Previous studies on OSA and glaucoma have reported mixed findings. This was a cross-sectional comparative study with a study duration of one year to compare the incidence of high intraocular pressure among OSA subjects and non-OSA subjects. This study took place in a tertiary hospital where a total of 50 subjects with OSA and 50 non-OSA subjects were recruited. The average age was 37 years (19,65) in a multiethnic study population (76% (Malay), 18% (Chinese) and 6% (Indian)). All patients underwent a full night computer-assisted polysomnogram (SOMNOCheck Effort Weinmann, Hamburg, Germany), Epworth Sleepiness Scale (ESS), Mullers manouevre (MM) to assess the level of obstruction and tonometry. The incidence of high Intra Ocular Pressure (IOP) among OSA subject was 52% with a significant difference between non-OSA and OSA subjects. Correlation between ESS and IOP were significant (p<0.05) for both eyes. There was a significant difference in mean IOP between non-OSA and OSA subjects for both eyes (p<0.05). A significant association was found between the presence of collapse at retropalatal and retrolingual region with high IOP (p<0.05). The incidence of high IOP among OSA patient (52%) provides a new insight in the management of patients with OSA. Significant associations exist between OSA parameters (ESS and presence of collapse on Mullers manouevre) and high IOP. We strongly recommend periodic ophthalmic assessment of intraocular pressure in patients with OSA.